(untitled) (Development Service Industry Management, 2025)
The article explores the essence of emotional intelligence and its importance for the formation of effective leadership in modern organizations. The impact of a manager’s emotional competence on personnel management, the formation of a healthy microclimate in the team and increasing labor productivity is analyzed. Modern approaches to the development of emotional intelligence as a tool for adaptive, ethical and communicative leadership are considered. Special attention is paid to the role of emotional intelligence in crisis situations and when making managerial decisions. Practical recommendations are given for the development of emotional competence of managers. Іn today’s conditions of globalization, digitalization and dynamic changes in the business environment, the effectiveness of organizations largely depends not only on the strategic vision of the leader, but also on his ability to manage people, create a favorable atmosphere in the team and direct the team to achieve common goals. Traditional approaches to leadership, which were based mainly on administrative levers of influence, are increasingly proving to be insufficient in the conditions of growing complexity of interpersonal interactions. In this context, the problem of developing emotional intelligence as an important factor in the formation of an effective leader is becoming increasingly relevant. Scientific research and practical observations show that a high level of emotional competence of a leader ensures better adaptation to changes, more productive team interaction, a decrease in the level of conflict and an increase in the overall level of employee satisfaction. Despite the growing attention to this topic, in the Ukrainian scientific and managerial discourse, the issue of integrating emotional intelligence into the leadership and personnel management system still requires thorough study. There is a need to formulate clear approaches to the development of emotional intelligence in managers, to substantiate methods for its assessment, and to study the impact of emotional intelligence on the effectiveness of management decisions and the performance of organizations.